PENCEGAHAN DAN PENGENDALIAN HIPERTENSI PADA LANSIA DI DUSUN SEMPALI DESA TUMPATAN KECAMATAN BERINGIN KABUPATEN DELI SERDANG - Wasliati, Balqis; Melissa, Melissa; Anindya, Nabila; Simamora, Nurul Iszhar Hairyah; Handayani, Putri; Nasution, Raihana Azzahra; Ayu, Shindy Dwi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Hypertension has become a health problem in the world because it has become a major risk factor for cardiovascular disease and stroke. 7.5 million deaths or around 12.8% of total deaths in the world are caused by hypertension. Currently hypertension is a big challenge in Indonesia because it is a condition that is often found. As many as 5.52% of the population in North Sumatra suffer from hypertension and 4.97% of the population in Medan City suffer from hypertension (Hesti Despita Siregar et all, 2021). Hypertension also affects many residents in Tumpatan Village. Tumpatan Village is one of the villages located in Beringin District, Deli Serdang Regency which has 8 hamlets. Sempali Hamlet is one of the hamlets that has a high prevalence of hypertension, especially in the elderly. So it is something that must be prevented so that its prevalence does not increase. The prevalence rate of hypertension is also caused by the lifestyle of the people there and the burden on their minds, which can cause high blood pressure in people, especially the elderly. So it is necessary to hold community service activities. This community service activity is carried out in the form of a seminar using the lecture method by providing counseling or education as well as by distributing leaflets and filling out questionnaires by activity participants. The participants in this outreach activity were 30 elderly people from Sempali Hamlet, Tumpatan Village, Beringin District, and it was carried out on December 16 2023. It is known that the significant value is p 0.000 (p<0,05). So it can be concluded that there is an influence of providing hypertension counseling on the knowledge of participants in PKM activities, the results of which are known after giving pre-test and post-test questionnaires to participants in PKM activities. Community service activities in the form of counseling about the prevention and control of hypertension in the elderly show that there is an influence of providing counseling on the knowledge of elderly people regarding hypertension. Based on this, it is hoped that the elderly can prevent and control hypertension so that it does not cause complications from various other diseases